The Roger Kahn reader : six decades of sportswriting - Kahn, Roger (University of Nebraska Press, 2018)
"A rich collection of fifty-one stories and articles by Roger Kahn. Written across six decades, this volume shows Kahn's ability to describe the athletes he profiled as they truly were in a manner neither compromised nor cruel but always authentic and up close"--